The Problem of Legitimation of the Proposition Cogito Ergo Sum - Noreika, Alvydas (Problemos, 2000)
This article deals with one of central problem of Cartesian philosophy – that of connection between thinking and being supposed by proposition cogito ergo sum. The problem is: By which operation of mind can we perceive connection between cogito and sum – whether by intuition, or deduction? In short, whether this proposition is a syllogism, or not? According to Descartes, the connection is perceived by straight insight of mind. But logical operator ergo existing between cogito and sum shows that cogito – the premise, sum is the conclusion, and proposition cogito ergo sum – is an abridged syllogism or an entimema (omitted general presupposition is “Everyone, who thinks, exists”). Descartes agrees that it is possible to think the general presupposition prior to the proposition. But in order to avoid the pitfall of syllogistic structure he uses analogy with problem of universalia. The general presupposition is a generality, and the proposition is an individuality. We know the individuality prior to the generality. Nevertheless, the connection is grounded by syllogism. The proposition is an entimema. Omitted general presupposition is “Every accidens points to substantia (as being and entity)”.